How Foraging Mode Sculpts Sensory Systems: Morphological Evidence From DiceCT and Histology in Sympatric Lizards - Lin Leng; Lei Shi (Ecology and Evolution)
ABSTRACT The relationship between foraging modes and sensory system morphology is critical for understanding the ecological and evolutionary adaptations of lizards. This study investigates the nasal olfactory system (NOS) and vomeronasal system (VNS) of four sympatric lizards from the Turpan Basin, China, which exhibit distinct foraging strategies: the active foraging Eremias roborowskii (Lacertidae), the sit‐and‐wait foraging Phrynocephalus axillaris (Agamidae) and Tenuidactylus dadunensis (Gekkonidae), and the seasonally frugivorous Teratoscincus roborowskii (Sphaerodactylidae), which adopts active foraging during fruit‐searching. Using diffusible iodine‐based contrast‐enhanced computed tomography (DiceCT) and histological sections, we compared the morphology and histology of their NOS and VNS. The results showed significant differences in the nasal cavity and vomeronasal organ structures: active foraging species (E. roborowskii and T. roborowskii) exhibited an enlarged nasal cavity with well‐developed lateral nasal conchae, thicker olfactory epithelium (OE), and higher densities of olfactory receptor cells compared to sit‐and‐wait foraging species. The VNS of active foraging lizards also showed thicker vomeronasal sensory epithelium (VSE) and greater vomeronasal receptor cell densities, particularly in E. roborowskii. In contrast, sit‐and‐wait foraging P. axillaris displayed reduced nasal conchae, thinner OE and VSE, and fewer receptor cells. Interestingly, the seasonal active foraging T. roborowskii demonstrated NOS enhancements akin to obligate active foraging species, suggesting a link between fruit detection and olfactory specialization. These findings support the hypothesis that foraging modes drive morphological divergence in the olfactory systems of lizards, highlighting the role of sensory adaptations in ecological niche specialization. This study provides novel insights into the coevolution of sensory structures and foraging behavior in sympatric lizards. Further studies are needed to explore the functional implications of these morphological differences.